Couples' shared experiences of dementia: a meta-synthesis of the impact upon relationships and couplehood. (3rd May 2016) - Wadham, Olivia; Simpson, Jane; Rust, Jonathan; Murray, Craig
Abstract : Objectives: There is a growing recognition of dementia as a condition that affects both members of a couple individually while also influencing the relational bond between them. This is an area which potentially has important service implications. Accordingly, the aim of this review was to elaborate the experience of dementia on partner/spousal relationships through a synthesis of pertinent qualitative literature. Method: A systematic literature search for qualitative research papers was undertaken in November 2013. Five databases (Academic Search Complete, CINAHL, MEDLINE, PsycARTICLES and PsycINFO) were searched using terms for dementia, partner and qualitative data analysis. Meta-synthesis was conducted on the data within the found papers. Results: A line-of-argument synthesis of 10 studies yielded four overarching themes, which highlight couples' efforts to maintain their sense of togetherness; shifts in balance and power within their relationship which can impact upon both partners' sense of identity; the empathy and sensitive attunement between couples as they work to protect each other's sense of role and identity; and the resilience couples demonstrate in the face of great fear, uncertainty and hopelessness. Conclusion: Findings have important implications for both research and practice, particularly the need for services to support couples' efforts to enhance couplehood in spite of dementia. Ultimately, this review adds further weight to arguments to refocus dementia care on relationships in addition to individuals.